Characterization of nano precipitate phase in an as-extruded Zn-Cu alloy. (15th July 2021) - Jiang, Jimiao; Huang, Hua; Niu, Jialin; Jin, Zhaohui; Dargusch, Matthew; Yuan, Guangyin
Abstract: Zn-Cu-based alloys are an important alloy series and show promising application prospect for biodegradable cardiovascular stents due to their excellent anti-self-aging property and combination of strength and ductility as well as good biocompatibility. Generally, nano-precipitates are an effective way to strengthen these alloys. In Zn-Cu-based alloys, only the second phases with submicron or micron size were observed in previous investigations. Here nanosized precipitates in an as-extruded Zn-2.0wt.%Cu alloy were first characterized using transmission electron microscopy, and identified as the ε (CuZn4 ) phase enriched Cu element with a hexagonal structure, which present with a rod shape and are symmetrically distributed along the [ 02 2 ¯ 1 ] η direction at a specific angle with the basal plane of the matrix. The nano-precipitates exhibit an approximately coherent interface with the matrix. The shape and orientation relationship with the matrix of these nano-precipitates were analyzed based on free energy minimization. Graphical abstract: Image, graphical abstract